Revenue generation in collegiate athletics: an exploratory case study of name, image, and likeness (NIL) compensation for the community college student-athlete - Craig, Jonathan Parker (Kansas State University, 2023)
In the last several decades, revenues for intercollegiate athletic programs in Power 5 Conferences have reached levels of corporate business. As these revenues have soared, criticism from the public has increased and “the most repeated complaint about college athletics is that it is a “business” or “commercial activity” (Osborne, 2014, p. 143). Sources of this revenue include industries such as merchandising, media, broadcasting, and video games. Over time, student-athletes have become aware that their image or likeness is being commercialized in these industries for private profit. Therefore, questions arose about the labor of student-athletes and if they are being exploited in an industry in which administrators, coaches, and institutions generate millions of dollars in revenue while student-athletes are prohibited from accepting compensation under the National Collegiate Athletic Association (NCAA) rules for amateurism. From this mounting pressure, a lawsuit was filed by a former student-athlete, Shawn Alston, that claimed the NCAA’s rules for amateurism were in violation of Section 1 of the Sherman Act. This case reached the Supreme Court of the United States (SCOTUS) in the summer of 2021 with SCOTUS ruling in favor of Alston. As a result, the NCAA was forced to suspend the rules of amateurism in adopting interim policy for the use of a student-athletes Name, Image, or Likeness (NIL). Therefore, as NIL policy is put into practice within intercollegiate athletics, it is anticipated that opportunities will flow down to all levels, including community colleges. The following exploratory multiple case study describes the perceptions of presidents, athletic directors, men’s and women’s basketball coaches, and men’s and women’s basketball student-athletes at three Midwestern community colleges for how NIL policy could affect the student-athlete experience at community colleges.
Keywords: Name, image, and likeness; Student-athlete; Amateurism; Community college; National Collegiate Athletic Association; National Junior College Athletic Association